A potential gateway to understanding liver disease development: peripartum lipid fluctuations in dairy cows - Vogel, Laura; Güttler, Markus; Theinert, Kirsten B.; Snedec, Teja; Reichelt, Kristin; Pietsch, Fabian; Schären-Bannert, Melanie; Rachidi, Fanny; Dobeleit, Gabriele; Fuhrmann, Herbert; Spilke, Joachim; Edlich, Frank; et al. (Frontiers in Cell and Developmental Biology, 2024)
Current lifestyles are leading to a worldwide increase in metabolic liver diseases that favor the development of liver disease. Changes in hepatocytes are caused by altered lipid concentrations, oxidative stress or toxicity by individual lipids. The complexity of the underlying processes and differences of the pathology to proposed rodent models makes the development of an effective targeted therapy difficult. The lipid mobilization that occurs in dairy cows in the postpartum period could be a natural model for the metabolic stress commonly observed in the development of liver diseases. We therefore used gas chromatography and histopathological staining techniques to analyze lipid patterns in diparous and multiparous cows during the peripartum period. The most striking change in lipid composition is the homogenous increase in palmitoleic acid (C16:1n7) content in all cows around the time of calving, with multiparous cows exhibiting consistently higher C16:1n7 levels by the end of the study. Elevated C16:1n7 levels have a potential key role in the development of non-alcoholic steatohepatitis (NASH) and tumorigenesis in the liver. Changes in C16:1n7, therefore, support the idea that lipid mobilization in dairy cows could serve as model for various liver diseases, such as nonalcoholic fatty liver disease (NAFLD) or NASH development.